Multi-objective optimization of a renewable power supply system with underwater compressed air energy storage for seawater reverse osmosis under two different operation schemes. (January 2022) - Zhao, Pan; Gou, Feifei; Xu, Wenpan; Wang, Jiangfeng; Dai, Yiping
Abstract: Water supply in rural islands or coastal areas is a basic task for people's livelihood. The all-pervading reverse osmosis (RO) technology is an energy-intensive process. To achieve sustainability goals, the development of renewable driven power supply system for RO plant is significant. Nowadays, the energy, economic and environmental indicators have rarely simultaneously investigated for the type of renewable power supply system with underwater compressed air energy storage (UW-CAES) for RO plant. In this paper, an energy-economic-environmental trade-off multi-objective optimization for such system is proposed in both grid-connected and off-grid schemes. A bi-level optimization strategy based on MOPSO algorithm and TOPSIS method is adopted to seek the optimal configuration and energy management strategy. A real-world case is implemented to demonstrate this method. The results show that the TPC/COE/EC set in optimal grid-connected scheme system is 3.716 × 10 6 ¥/0.814¥kWh −1 /795.922 kg with a configuration of 511 PVs, 12 WTs and a 900 m 3 bag volume in UW-CAES. Whereas, the TPC/COE/EC in optimal off-grid system is 4.076 × 10 6 ¥/2.305 kWh −1 /566.254 kg with a 705/8/900 m 3 configuration. In energy perspective, both schemes can match the load well. In economic perspective, the grid-connected scheme has a considerable profit, whereas the off-grid has no revenue. In environmental perspective, both schemes can reduce the carbon emission remarkably.